Pengaruh Disiplin dan Kemampuan Kerja terhadap Kinerja Pegawai Dinas Kesehatan Kabupaten Konawe Selatan - Resky, Kartika; Breemer, Yacob (Attractive : Innovative Education Journal, 2023)
This research aims to find out and analyze: (1) To study and determine simultaneously the influence of work discipline and ability on the performance of employees of the South Konawe Regency Health Service (2) To study and determine the influence of work discipline on the performance of employees of the South Konawe Regency Health Service (3) ) To study and determine the influence of ability on the performance of South Konawe District Health Service employees. The sample used in this research was 113 respondents who were employees at the South Konawe District Health Service. The analysis technique used was descriptive statistical techniques and inferential statistics. The analysis used to answer the hypothesis in this research is multiple linear regression analysis. The results of the research obtained several conclusions, namely (1) Discipline and work ability simultaneously have a significant effect on employee performance. Increasing discipline and work ability has a real effect on improving employee performance. The more disciplined the employees are and supported by good employee work abilities, the higher the performance of the South Konawe District Health Service employees (2) Discipline has a positive and significant effect on employee performance. Increasing discipline in a positive and real direction towards improving employee performance. The better the discipline, the higher the performance of the South Konawe District Health Service employees (3) Work ability has a positive and significant effect on employee performance. Increasing work ability in a positive and real direction towards improving employee performance. The better the work ability, the higher the performance of the South Konawe District Health Service employees. Keywords: Discipline and Work Ability, Work Dicipline